Effects of a 12-Week Skipping Exercise Program on Leg Endurance in Competitive Badminton Players: A Randomized Controlled Trial - Irena, Ririn; Melati, Ardila; Geanta , Vlad Adrian; Simbolon, ⁠Ayu Mayzura; Foret , Retha (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2025)
The purpose of the study. Leg endurance is vital for badminton, yet training methods for its enhancement are inadequately explored. This study examined the impact of a skipping exercise regimen on leg endurance and performance metrics among competitive badminton athletes. Materials and methods. A total of sixty competitive badminton athletes enrolled badminton players from regional clubs and university in North Sumatera Indonesia, with a mean age of 21.5 ± 1.7 years, were systematically assigned to either an intervention group (n=30) or a control group (n=30) through a randomization process. The participants in the intervention cohort undertook a 12-week progressive skipping exercise program in conjunction with their regular badminton training, whereas the control group adhered solely to standard training protocols. The primary outcome measures comprised a badminton-specific endurance assessment and the 30-second Wingate test, while secondary outcome parameters included evaluations of agility, jump performance, and movement dynamics on the court. Results. The intervention cohort exhibited significant enhancements across all metrics relative to the control group (p < 0.001). Notable effect sizes were recorded for the badminton-specific endurance test (d = 1.32), Wingate peak power (d = 1.17), and mean power (d = 1.25). Secondary outcomes also reflected considerable advancements, including agility (d = 1.08-1.13), jump performance (d = 1.03-1.10), and on-court movement patterns (d = 1.07-1.16). Strong correlations were identified between leg endurance improvements and badminton-specific performance metrics (r = 0.65-0.73, p < 0.001). Conclusions. The 12-week skipping exercise program markedly improved leg endurance and related performance metrics in competitive badminton players. These results indicate that skipping exercises constitute an effective, versatile, and sport-specific training approach for enhancing physical readiness in badminton. Coaches and athletes are encouraged to integrate structured skipping programs into their training routines to elevate badminton-specific physical performance.